Comparison of quantitative lung computed tomographic findings between idiopathic pulmonary fibrosis patients diagnosed by biopsy and by multidisciplinary discussion without biopsy - Gökçek, Atila (The European Research Journal, 2022)
Objectives: We aimed to investigate the objective quantitative differences between the parenchymal computed tomography (CT) findings of idiopathic pulmonary fibrosis (IPF) patients diagnosed by surgical lung biopsy and by multidisciplinary discussion without biopsy. Methods: We performed parenchymal texture analyses in lung CT images of 116 IPF patients, 42 diagnosed by surgical lung biopsy, and 74 by multidisciplinary discussion without biopsy. The relative volumes of the ground-glass, reticular, honeycomb, hyperlucent, and normal parenchymal patterns were measured in six predefined sections of each lung by an automatic texture analysis software (CALIPER: Computer-Aided Lung Informatics for Pathology Evaluation and Rating). The results were compared between the two patient groups. Results: When the relative volumes of the parenchymal patterns were compared between the biopsied and non-biopsied groups in a total lung-based manner, the mean percentage of only the ground-glass pattern was significantly higher in the biopsied group. When compared between the corresponding lung sections, the percentages of the ground-glass pattern were higher in the biopsied group than those in the non-biopsied group at the bilateral central sections of the upper, middle, and lower lung zones. At the bilateral peripheral sections of the middle and lower lung zones, the sectional reticular pattern percentages were lower in the biopsied group than those in the non-biopsied group. Conclusions: CALIPER’s quantitative CT measurements revealed that the sectional relative volumes of the ground-glass and reticular patterns, but not of the honeycomb, normal, and hyperlucent parenchyma, were significantly different between some of the corresponding lung sections of the biopsied and non-biopsied IPF patients. This information may help a better understanding of the role of the CT findings in biopsy decisions and avoiding some of the unnecessary biopsies in suspected IPF patients.